How Gut Microbiome Signatures Shape Metformin Response and GI Intolerance in Type 2 Diabetes - Sari, Lia Nur Indah; Idrus, Citra Lorenza (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Metformin is first-line therapy for type 2 diabetes mellitus (T2DM), yet interindividual variability in glycaemic response and frequent gastrointestinal (GI) intolerance are not fully explained by pharmacogenomics alone. This review synthesised evidence that links baseline gut microbiome composition to metformin effectiveness and tolerability. English-language, open-access Human observational studies from the past decade were identified in PubMed, ScienceDirect, and Google Scholar if they reported stool- or rectal sample–derived microbiome profiles alongside glycaemic outcomes (e.g., HbA1c change) or GI adverse events, dose modification, or discontinuation, with standardised extraction of design, population, -omics methods, and outcome definitions. Few eligible studies met criteria; across prospective and cross-sectional cohorts, higher alpha diversity and specific taxa—including Akkermansia and Streptococcus—were associated with increased GI adverse events to metformin, while distinct microbial signatures differentiated glycaemic responders from non-responders. A small multi-omic analysis suggested that shifts in bile acid–related bacteria together with down-regulation of anti-inflammatory host genes may underlie intolerance. Integrative models combining pharmacogenomic variants with microbiome features were rarely evaluated, and head-to-head comparisons with pharmacogenomics-only models are lacking. Overall, baseline gut microbiome signatures correlate with variability in metformin responses and GI intolerance in T2DM, underscoring the need for larger, standardised multi-omic cohorts to quantify the incremental predictive value of microbiome data for personalised metformin theraphy.